Teak the Intruder Vis-a-vis Occurrence of Teak in Sal Forests of Bastar - Tiwari, S. D. N. (Indian Forester, 1954)
In the territory of old Bastar state teak and sal forests are found in two separate zones. Apart from the merging zone, teak is found scattered and in patches in the heart of the sal zone. In this short article the author tries to establish that this teak has been introduced by man specially on account of Royal patronage the Ruler having come from the teak area of the South. Profuse regeneration of teak in all such scattered patches is seen and sal is being replaced at many places so much so that one may be misled to believe it to be natural. Many deductions have been drawn from this study - some of the important ones being that sal had wider distribution in the past and its territory is being curtailed at many places; secondly in evolution sal which belongs to a much older family than teak will gradually be replaced by teak and thirdly, teak plantations in the sal zone should normally be successful specially in those areas where ecological factors are favourable.